Gut microbiota and intestinal immunity interaction in ulcerative colitis and its application in treatment - Bu, Fan; Chen, Kaiyuan; Chen, Siche; Jiang, Yi (Frontiers in Cellular and Infection Microbiology, 2025)
Ulcerative colitis (UC) is a chronic, non-specific inflammatory bowel disease characterized by inflammation and injury of the colonic mucosa, exhibiting an increasing global incidence. Although research into UC pathogenesis is ongoing, the precise mechanisms remain to be fully elucidated. Studies indicate that UC development results from a complex interplay of factors, including genetic predisposition, environmental exposures, gut microbial dysbiosis, and immune dysregulation. Specifically, UC pathogenesis involves aberrant immune responses triggered by interactions between the host and gut microbiota. A complex, dynamic relationship exists between the microbial community and the host immune system throughout UC pathogenesis. Accumulating evidence suggests that changes in microbiota composition significantly impact gut immunity. This review will examine the intricate balance between the gut microbiota and mucosal immunity in UC progression and discuss potential therapeutic applications, providing a reference for further clinical treatment of this patient population.